Szkice do socjologicznego portretu współczesnej młodzieży (wybrane zagadnienia) = Sketches for a sociological portrait of contemporary youth (selected issues) - Sroczyńska, Maria (Zielona Góra: Lubuskie Towarzystwo Naukowe)
This article reflects on the sociological sketch for the "portrait" of Polish youth, mainly Generation Z, who are coming of age against a background of multiple crises. The sources of information include both literature review and first-hand data collected by the author. The theses formulated are tentative, as they reveal certain "impotence" when trying to present the social consequences of the crises that accompany becoming an adult.
Keywords: sociological sketch; youth; specificity of Generation Z; axiological context; szkic socjologiczny; młodzież; specyfika pokolenia Z; kontekst aksjologiczny